Applications in Unusual Contexts in Engineering Mathematics: Students’ Attitudes - Gruenwald, N; Sauerbier, G; Narayanan, A; Klymchuk, S; Zverkova, T (Mathematics Teaching-Research Journal (MTRJ), 2010)
This paper presents results of three studies on using an innovative pedagogical strategy in teaching mathematical modelling and applications to engineering students. The studies analyse engineering students’ attitudes towards non-traditional for them contexts in teaching/learning of mathematical modelling and applications: environment, business and epidemics. The first study deals with using differential equations in the environment and ecology. The second study deals with using linear programming for maximizing profit and minimizing expenses for a company. The third study deals with using differential equations for making a prediction of a number of cases in an epidemic. Analysis of students’ responses to questionnaires, their comments and attitudes towards the innovative approach in teaching are presented in the paper.